Correction: Promoting physical activity in geriatric patients with cognitive impairment after discharge from ward-rehabilitation: a feasibility study. - Eckert, Tobias; Bongartz, Martin; Ullrich, Phoebe; Abel, Bastian; Werner, Christian; Kiss, Rainer; Hauer, Klaus (European Journal of Ageing, 2026)
The article addresses a correction regarding the proper structuring of the name of an author, Christian Werner, in a previously published work. It clarifies that the name was displayed correctly in all versions at the time of publication, and it emphasizes the importance of accurate author attribution in academic literature. The correction serves to maintain the integrity of the publication and ensure proper recognition of contributors. Additionally, the publisher, Springer Nature, reaffirms its neutrality concerning jurisdictional claims in published maps and institutional affiliations.